Jane Tolmach Campaign Statement
This campaign statement presents Jane Tolmach as an experienced and effective candidate committed to strong representation for Ventura County in Sacramento. She emphasizes tax reform and property tax relief, arguing that the state must stop shifting financial burdens onto local property owners and ensure Ventura County receives its fair share of state revenues, including transportation funds. Tolmach also calls for reducing costly bureaucracy, particularly at the regional level, and improving efficiency in government services. She strongly supports establishing a four-year state college in Ventura County and identifies unemployment as the state's most serious economic problem, pledging to promote job growth and economic stability.